2005
DOI: 10.1128/mcb.25.24.10965-10978.2005
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Sept6, a Fusion Partner Gene of MLL, Does Not Affect Ontogeny, Leukemogenesis Induced by MLL-SEPT6, or Phenotype Induced by the Loss of Sept4

Abstract: Septins are evolutionarily conserved GTP-binding proteins that can heteropolymerize into filaments. Recent studies have revealed that septins are involved in not only diverse normal cellular processes but also the pathogenesis of various diseases, including cancer. SEPT6 is ubiquitously expressed in tissues and one of the fusion partner genes of MLL in the 11q23 translocations implicated in acute leukemia. However, the roles of this septin in vivo remain elusive. We have developed Sept6-deficient mice that exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 59 publications
2
49
0
Order By: Relevance
“…As the central subunit in this septin complex, SEPT2 cannot be replaced in the conditions tested (15). Conversely, it has been proposed that members of the SEPT6 group are interchangeable, at least in the context of the SEPT2-SEPT6-SEPT7 complex (3,12). Thus, some of the phenotypes we observe here in cells depleted for SEPT11 could be because the SEPT6 group members are partially redundant.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…As the central subunit in this septin complex, SEPT2 cannot be replaced in the conditions tested (15). Conversely, it has been proposed that members of the SEPT6 group are interchangeable, at least in the context of the SEPT2-SEPT6-SEPT7 complex (3,12). Thus, some of the phenotypes we observe here in cells depleted for SEPT11 could be because the SEPT6 group members are partially redundant.…”
Section: Discussionmentioning
confidence: 71%
“…Widely expressed in mammalian tissues (10), SEPT11 may also be a substitute for SEPT6 in other mammalian septin complexes such as SEPT7-SEPT9-SEPT11 (10) or SEPT5-SEPT7-SEPT11 (11). Because other septins homologous to SEPT11 might compensate for its deficiency (12), the degree to which SEPT11 is required for septin filament structure and function is not yet known. Listeria monocytogenes is an invasive bacterium that enters into most mammalian cells in vitro through the interaction of the bacterial surface protein InlB with its host cellular receptor Met, the hepatocyte growth factor receptor (13).…”
mentioning
confidence: 99%
“…It has been reported that a septin 4 null mouse has a phenotype, including male infertility and anatomical abnormalities of the cerebellum (13,66). However, the knock-out septin 3, septin 5, or septin 6 mice showed no apparent effect on brain phenotype (7,66,67), indicating that there is developmental compensation and/or functional redundancy of various septins.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of FLT3 in these cells were evaluated using a phycoerythrin (PE)-conjugated anti-CD135 antibody, or an anti-mouse immunoglobulin G1,k, as the isotype-matched control (BD Biosciences, San Diego, CA, USA) using fluorescence-activated cell sorting (FACS) Calibur (BD Biosciences) as described earlier. 33 …”
Section: Cellsmentioning
confidence: 99%
“…Morbid mice and their tissue samples were analyzed, and immunophenotyping of BM, splenic and thymic cells was performed using the FACS Calibur, as described earlier. 33 The hematopoietic neoplasms were diagnosed mainly on the basis of morphology as described earlier. 6 The probabilities of murine overall survival were estimated using Kaplan-Meier method and compared using the log-rank test.…”
Section: Leukemogenesis Assays In Vivomentioning
confidence: 99%